1995
DOI: 10.1016/s0022-5347(01)66936-2
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Blockade in the Treatment of Symptomatic Benign Prostatic Hyperplasia

Abstract: alpha-Blockers were beneficial in the treatment of benign prostatic hyperplasia. Tolerance to treatment appeared to develop in a large proportion of patients after 6 months of therapy. However, for patients who benefit from long-term use of alpha-blockers effective treatment might be maintained for years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The mean improvement in total symptom score is estimated < 39% for patients receiving a 1 -AR antagonists and < 25% for those receiving placebo, i.e. a difference of < 14% [16]. Patients receiving a 1 -AR antagonists perceived the reduction in symptom score as a`moderate' level of improvement.…”
Section: Pathophysiology Of Lutsmentioning
confidence: 99%
“…The mean improvement in total symptom score is estimated < 39% for patients receiving a 1 -AR antagonists and < 25% for those receiving placebo, i.e. a difference of < 14% [16]. Patients receiving a 1 -AR antagonists perceived the reduction in symptom score as a`moderate' level of improvement.…”
Section: Pathophysiology Of Lutsmentioning
confidence: 99%
“…1-adrenoceptor (AR) antagonists, 5alpha-reductase inhibitors and phytotherapy seem to be useful for improvement of the current therapy. 1-adrenoceptor antagonists relieve symptoms by relaxing prostatic smooth muscle by blocking stimulation of postjunctional 1 -adrenoceptors [88,89]. Previous studies on human prostate suggest that the response to electrical field stimulation is almost completely suppressed by -adrenoceptor antagonists [90][91][92].…”
Section: P2 Receptors In Prostatementioning
confidence: 99%
“…Furthermore, by radioligand binding, it has been shown that that main subtype of α 1 -adrenoceptor is α 1Α (Wada et al 1996). It has been suggested that part of the beneficial effects of α 1 -adrenoceptor antagonists in patients with benign prostatic hyperplasia (Eri and Tveter 1995), is exerted at spinal/supraspinal sites (Andersson, 1995). Since indoramin has selectivity for the α 1A -adrenoceptor subtype (Forray et al 1994), whereas most clinically used α 1 -adrenoceptor antagonists, including doxazosin, have no subtype selectivity (Forray et al 1994), indoramin was chosen for investigation.…”
Section: Effect Of Intravesically Infused Capsaicinmentioning
confidence: 99%
“…Indoramin and other α 1 -adrenoceptor antagonists have been successfully used for alleviation of symptoms in patients with benign prostatic hyperplasia (Eri and Tveter 1995), and it has been suggested that part of their effects is exerted at spinal/supraspinal sites (Andersson 1995). Indoramin has selectivity for the α 1A -adrenoceptor subtype, whereas most clinically used α 1 -adrenoceptor antagonists, including doxazosin, have no subtype selectivity (Forray et al 1994).…”
Section: Introductionmentioning
confidence: 99%